404 Can MRI Non-Invasively Measure Blood-Brain-Barrier Permeability?. (28th February 2022) - Ali, T.; Blamire, A.; Parikh, J.
Abstract: Aim: Blood brain barrier (BBB) integrity in neurological disease is tested with gadolinium-enhanced Magnetic Resonance Imaging (MRI). Pathology studies have shown gadolinium deposits in brains with intact BBBs, thus raising concern. We propose a novel use of Arterial Spin Labelling (ASL) –a MRI technique which 'tags' blood-water making it a tracer– as a safer alternative in assessing BBB permeability. ASL's ability to capture T2 (transverse relaxation time) changes of tagged water in blood vs. in tissue (post-exchange across the BBB) supports its feasibility. Method: We developed an ASL protocol and collected data from healthy volunteers (n=5) on a 3T Achieva Scanner with the parameters: echo times (TEs) 30, 40, 50, 60, 70ms; repetition time 4200ms; field of view 240x240x47mm and post label delays (PLDs) 1, 000ms and 1, 500ms. We calculated mean ASL signal (arb units) from the images at each TE, and then extracted T2(ms) values for each volunteer at each PLD. The primary outcome was the change in T2 across PLDs. Results: Calculated mean T2s demonstrated a majority of increasing T2s across longer PLDs (n=3) with mean T2 of 55.3+ 5.3ms at PLD 1, 000ms and 62.1+ 10.8ms at PLD 1, 500ms. However, the results are inconclusive as the sample size precluded statistical testing. Conclusions: We developed an ASL protocol that demonstrated changes in T2 of blood water with time passage, indicating water exchange through the BBB. This supports the use of ASL in assessing BBB permeability, but more wide-scale studies need to be performed.